Construction industry advance and change : progress in eight Asian economies since 1995 - Anson, Michael; Chiang, Yat Hung; Lam, Patrick; Shen, Jianfu (Emerald Publishing Limited, 2021)
A nation's construction industry is essentially home grown, a derivative of its culture, history, geography and economic circumstances with every building or road a unique product, always a prototype, unlike the honed prototypes set up for efficient production runs of other industries. In terms of what was built and the standards achieved, Construction Industry Advance and Change: Progress in Eight Asian Economies since 1995 describes construction industry progress between 1995 and 2019 in Hong Kong , India, Indonesia, Japan, Malaysia, South Korea, Sri Lanka and Vietnam. The 25-year accounts provide insight into the nature of these individual construction industries, their shared characteristics, and their differing priorities. The book will add knowledge and contextual reference for construction industry professionals, public policy makers and academic researchers studying the industry. New students in construction industry management courses, will find the information and context needed to appreciate the nature of construction industries and the factors affecting industry output performance.